Tumor microenvironment-responsive fluorogenic nanoprobe for ratiometric dual-channel imaging of lymph node metastasis - Cho, Hong-Jun; Lee, Seokyung; Park, Sung-Jun; Lee, Yong-Deok; Jeong, Keunsoo; Park, Jae Hyung; Lee, Yoon-Sik; Kim, Bokyung; Jeong, Han-Sin; Kim, Sehoon (ELSEVIER SCIENCE BV, 2019)
Fluorogenic nanoprobes capable of providing microenvironmental information have extensively been developed to improve the diagnostic accuracy for early or metastatic cancer detection. In cancer-associated micro environment, matrix metalloproteinase-2,9 (MMP-2,9) has drawn attention as a representative enzymatic marker for diagnosis, prognosis, and prediction of various cancers, which is overexpressed in the primary site as well as metastatic regions. Here, we devised dual-emissive fluorogenic nanoprobe (DFNP) emitting both MMP-2,9-sensitive and insensitive fluorescence signals, for accurate monitoring of the MMP-2,9 activity in metastatic regions. DFNP was nanoscopically constructed by amphiphilic self-assembly between a constantly fluorescent polymer surfactant labeled with Cy7 (F127-Cy7) and an initially nonfluorescent hydrophobic peptide (Cy5.5-MMP-Q) that is fluorogenic in response to MMP-2,9. Ratiometric readout (Cy5,5/Cy7) by dual-channel imaging could normalize the enzyme-responsive sensing signal relative to the constantly emissive internal reference that reflects the probe amount, allowing for semi-quantitative analysis on the MMP-2,9-related tissue micro environment. In addition to the dual-channel emission, the nanoconstructed colloidal structure of DFNP enabled efficient accumulation to lymph node in vivo. Because of these two colloidal characteristics, when injected intradermally to a mouse model of lymph node metastasis, DFNP could produce reliable ratiometric signals to provide information on the MMP-2,9 activity in the lymph nodes depending on metastatic progression, which corresponded well to the temporal histologic analysis. Furthermore, ratiometric lymph node imaging with DFNP after photodynamic therapy allowed for monitoring a therapeutic response to the given cancer treatment, demonstrating diagnostic and prognostic potential of the nanoconstructed colloidal sensor of tumor micro environment in cancer treatment.
Keywords: MATRIX METALLOPROTEINASES; CANCER; NANOPARTICLES; INVASION